Моделювання мікроструктурованого оптичного волокна - Саєнко, Є. О. (ХНУРЕ, 2024)
Two-dimensional model of the microstructured optical waveguide has been developed in this work. Circular microstructured holes arranged in a circularly oriented setting around the core in this model. Perfectly matсhed layer is used as boundary condition on the outer part of the optical fiber. Spatial distributions of the electromagnetic field components have been obtained using numerical method of finite elements. Simulations results allow investigate the electromagnetic energy localisation efficiency within the microstructured optical fiber core.
Keywords: оптичне волокно